Raman Spectroscopy of TiO2 Nanoparticles Synthesized by Hydrolysis of TiCl4: Effect of Sulfate Ions Concentration - Lee, K.M. (Springer Science and Business Media B.V., 2021)
Titanium dioxide (TiO2) nanoparticles were synthesized via precipitation method. The objective of the work is to investigate the influence of ammonium sulfate concentration on the properties of as-synthesized and calcined TiO2 nanoparticles at room temperature. The concentrations were varied based on molar fraction of TiCl4:ammonium sulfate ranging from 20:1 to 0.5:1. The morphology and types of phases present in the samples were characterized using TEM, XRD and Raman spectroscopy. Titanium dioxide particles with pure anatase phase were successfully synthesized at 350Â â for 2Â h with crystallite size ranging from 22 to 67Â nm. Typical spherical shaped TiO2 particles were observed from TEM images. As the concentration of sulfate ions increased, the average crystallite size was found to decrease. Based on the Raman spectra, shifting of peak position (Eg mode) to lower wavenumber with decreased crystallite size was found to be different from other reported works. This may be caused by defects formed due to traces of sulfate ions coordinated to Ti(IV) surface atoms. The major anatase peaks such as 635Â cmâ1 (Eg mode) and 397Â cmâ1 (B1g mode) were found to be predominant in all uncalcined samples and the peaks intensity increased after calcination. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.